إزالة الفينول باستخدام بعض الأحياء الدقيقة (Tishreen University, 2019)
This research work addressed laboratory study for biological treatment of phenol. Figuring phenol disintegration will give an idea of biodegradation of most organic chemicals since it is included in the composition of most of them. Biological treatment is considered one of the effective and economic ways to address phenol treatment by biodegradation as compared with high cost methods of physical and chemical processing. The method is of low efficiency when applied to high concentrations, in addition to formation of secondary compounds that may be more dangerous than the target material. The study focused on use of three isolates, i.e. Pseudomonas, Chlorella and Acentobacter. They were taken from the Microbiology Studies Laboratory at Allepo University, and characterized by its resistance to phenol at concentrations that reached up to 600 mg/L. It was found that algae Chlorella genus is the best sample in the disintegration of phenol and the most resistant. It has been able to disintegrate more than 90% of the concentration of phenol in its media within two weeks. The study showed that a vaccine of 4% of the size of the media was enough to resist inhibiting effect to phenol. Best results were achieved the in biodegradation rates of phenol at the temperature range of ​​30 to 35°C, moderate pH (7 = pH) and ventilation at rotation speed of 125 rev/min, coupled with the best rate of growth after 48 hours of incubation. The research recommended to use microorganisms, that are characterized by resistance to phenol and its compounds and most capable of its disintegration of using it as the sole source of carbon and energy such as species of Pseudomonas, Acentobacter and Chlorella. يُعّد الفينول ومشتقاته اللّبنة الأساسية لمدى واسع من المواد العضوية العطرية الصنعية الخطرة والشائعة في مياه الصرف الصناعي، كما أنه يوجد في البيئة بشكل طبيعي فهو من المواد العطرية المنحلة بالماء وسهل الانتشار ضمن مكونات البيئة، وتكمن خطورة الفينول بمقاومته للتفكك، وبسميته حتى بالتراكيز المنخفضة؛ إضافة لتشكيل مركبات كلور الفينول عند معالجة المياه الحاوية عليه بالكلور حيث تملك هذه المركبات عتبات منخفضة لإدراك الطعم والرائحة. تطرق هذا البحث لدراسة مخبرية لإزالة الفينول بالمعالجة الحيوية، فدراسة تفككه تعطي فكرة عن تفكك أغلب المواد الكيميائية العضوية كونه يدخل في تركيب معظمها. تُعد طريقة المعالجة الحيوية من الطرق الفعالة والاقتصادية لمعالجة الفينول وذلك بالتفكك الحيوي، مقارنة مع المعالجة الفيزيائية والكيميائية المرتفعة التكاليف، والمنخفضة الفعالية عند تطبيقها على التراكيز العالية، إضافة لتكوينها لمركبات ثانوية ربما تكون أشد خطراً من المادة الهدف. انطلاقاً مما سبق ركزت الدراسة على استخدام ثلاثة عزلات وهي Pseudomonas،Chlorella Acentobacter حيث تم أخذها من مخبر دراسات الأحياء الدقيقة، وتميزت بمقاومتها للفينول بتراكيز وصلت حتى 600 ملغ/ل. وقد تبين أن الطحالب من جنس ال Chlorellaهي العينة الأفضل في تفكك الفينول والأكثرها مقاومة وقد استطاعت تفكيك أكثر من 90% من تركيز الفينول في مستنبتاتها خلال أسبوعين، و أظهرت الدراسة أن لقاحاً بنسبة 4% من حجم المستنبت كان كافياً لمقاومة التأثير المثبط للفينول، وتحققت أفضل نتائج في معدلات التفكيك الحيوي للفينول في المجال الحراري 30-35°م ودرجة الحموضة المعتدلة (7 =pH) والتهوية عند سرعة دوران 125 دورة/ دقيقة، مترافقةّ مع أفضل معدل للنمو بعد 48 ساعة من الحضن. وخلص البحث بتوصية استخدام الأحياء الدقيقة التي تتميز بمقاومتها للفينول ومركباته والأكثر قدرةً على تفككه واستخدامه كمصدر وحيد للكربون والطاقة كأنواع جنس الزائفة Pseudomonas spp. والـ Acentobacter والـ Chlorella.